IMPLEMENTASI METODE ROLE PLAY UNTUK MENSTIMULASI KEBERANIAN BERKOMUNIKASI INTERPERSONAL SISWA DI SEKOLAH DASAR - Yusuf Rendi Wibowo; Fatonah Salfadilah (PGSD STKIP PGRI Pacitan, 2026)
Interview learning in elementary schools requires interpersonal communication skills supported by students’ courage and self-confidence. However, instructional practices still tend to limit students’ opportunities to engage in authentic communication. This study aims to describe the implementation of the Role-Play method in stimulating the interpersonal communication confidence of fourth-grade students in Indonesian language interview learning. The research employed a qualitative descriptive approach conducted at SDN 1 Way Mili during the even semester of the 2024/2025 academic year. Data were collected through classroom observations, interviews with teachers and students, and documentation, and were analyzed qualitatively. The findings indicate that the Role-Play method enhances students’ confidence in expressing opinions, asking questions, maintaining eye contact, speaking more clearly, and responding to interlocutors. It can be concluded that Role Play is effective in creating communicative and contextual interview learning while supporting the development of elementary school students’ interpersonal communication confidence.